Ethics and Bioethics Education in Secondary Schools in Croatia - Jurić, Hrvoje, filozof (2010)
Bioethical contents in the Croatian educational system are taught not only at the university level, but also in secondary schools. Namely, in 1995, as an alternative to confessional religious teaching, the Ethics was introduced as a separate school subject. Present teaching program of Ethics came into the force in 2003. Ethics is taught during all the four years of secondary schools, while the third year is dedicated to bioethical topics only. This presentation will firstly try to explain the context of ethics and bioethics education in secondary schools in Croatia ; afterwards the teaching program of Ethics will be presented, with an accent on bioethical contents ; and finally, we will point to some problems with which the teaching of ethics and bioethics at this educational level is confronted.
Projekt MZOS
ENG